THE DEVELOPMENT OF MATHEMATICAL REASONING ABILITIES AND ATTITUDES USING THE CONCEPT OF EXPERIENTIAL LEARNING CYCLE AND BADHAM’S QUESTIONING TECHNIQUE OF GRADE 5 STUDENTS - Thuathong, Arphaphat; Sirithanyarat , Chintana; Yodsin, Naphaporn (Journal of MCU Phetchaburi Review, 2024)
Abstract The purposes of this research were to 1) compare Mathematical Reason Skill of grade 5 students before and after learning the Experiential Learning cycle with questioning techniques of Badham 2) to compare the attitude of grade 5 students after learning the Experiential Learning cycle with questioning techniques of Badham. The sample were 20 students by Simple Random Sampling from Wat Paikhad School on the second semester on the academic year 2023. The research instruments consisted of lesson plans, 3 Reason Skill achievement tests and the attitude of students after leaning with Mathematical. The statistics for data analysis were mean, standard deviate and t-test (dependent samples). The results were as follow 1) The Mathematical Reason Skill of grade 5 students before and after learning the Experiential Learning cycle with questioning techniques of Badham was higher than before learning with statistically significant at level of .05 2) The attitude of grade 5 students after learning the Experiential Learning cycle with questioning techniques of Badham was higher than before learning with statistically significant at level of .05